The Role of the Principal in Improving Teacher Performance in the Development of Evaluation of Learning Outcomes through Academic Supervision of Principals during the Covid-19 Pandemic - Suprapti Suprapti (Journal of Classroom Action Research, 2020)
The ability of teachers at SMA Negeri 8 Mataram is still very concerning, especially when evaluating learning outcomes. This is becoming increasingly worrying with the current condition, namely the Covid-19 Pandemic where all learning processes must be conducted online. The aim of this study was to determine whether the role of the principal through online academic supervision can improve teacher performance in evaluating learning outcomes at SMA Negeri 8 Mataram. This research is included in the School Action Research. At school, action research is conducted in 2 cycles. The results showed that in cycle I the percentage of teacher completeness was 28.12% and in cycle II the percentage of teacher achievement was 89.06%. The results of this study clearly indicate that the principal plays an important role in conducting academic supervision of teachers, especially in developing the evaluation of student learning outcomes. Therefore, it is concluded that coaching through the academic supervision of the principal can improve the performance of SMA Negeri 8 Mataram teachers in developing evaluation of learning outcomes with a completeness of greater than or equal to 85%